APPLYING AN ADD-IN “IMMERSIVE READER” TO OVERCOME DIFFICULTIES FOR LANGUAGE LEANERS SUFFERING FROM DYSLEXIA = ÁP DỤNG ỨNG DỤNG BỔ SUNG “IMMERSIVE READER” VÀO VIỆC CẢI THIỆN NHỮNG BẤT CẬP TRONG VIỆC HỌC TẬP NGÔN NGỮ CỦA NHỮNG SINH VIÊN MẮC CHỨNG KHÓ ĐỌC - Lê, Khánh Huyền (2020)
The research tries to serve two purposes: (1) list out the number of first-year students who stand a high chance of having dyslexia; (2) test the effectiveness of using Immersive Reader on improving Reading Fluency of those students. In order to achieve those two objectives, a combination of qualitative and quantitative research have been used. Specifically, a questionnaire adapted from an informal dyslexia screening has been used to find out the number of students who stand a high chance of being dyslexic. Besides, interviews and tests were also utilized in order to find out the effectiveness of the technological add-in tool. After the research, it was found out that there were four students who possessed items with high indicators of dyslexia. The results showed that using Immersive Reader to practice reading increased the accuracy and automaticity of word decoding which led to the improvement of reading fluency. Besides, it was also proved that Immersive Reader enhanced the user’s experience with reading.